PESQUISA BIBLIOMÉTRICA SOBRE HABITAÇÃO DE INTERESSE SOCIAL NO PERÍODO DE 2013 A 2014 - Sant'anna, Igor; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Brazil has a deficit of housing of relevant social interest. This article proposes, through a bibliometric review, to analyze quantitatively and statistically the scientific production that presents the terms "housing", "Interest", "Social", between the years of 2013 to 2017, as well as to identify the nuances and themes of such production. The review identified a large number of published articles, mostly concentrated in a single periodical, subdivided into four main themes, of which there is no viability or management.